Dickens''s Great Expectations. - Brinton, Ian (Reader''s Guides., 2007)
Reader''s Guides provide a comprehensive starting point for any advanced student, giving an overview of the context, criticism and influence of key works. Each guide also offers students fresh critical insights and provides a practical introduction to close reading and to analysing literary language and form. They provide up-to-date, authoritative but accessible guides to the most commonly studied classic texts. Great Expectations (1861) is not only one of the last great novels to be written by Dickens but is also one which centres around his primary themes: the importance of childhood in re.